Pokritja različnih algebrskih struktur - Lemut Furlani, Ajda (Matrika, 2021)
The article presents a well known covering problem. First somewhat generally, then on three algebraic structures, on groups, rings and vector spaces. In the last chapter, there is a generalization of the theorems from the chapter on vector spaces to affine spaces.
Keywords: afine spaces; algebra; covering problem; groups; pokritja afinih prostorov; pokritja grup; pokritja kolobarjev; pokritja vektorskih prostorov; problem pokritja; rings; vector spaces